?EFFECT OF SOWING DATE ON THE YIELD AND YIELD COMPONENTS OF SHORT DURATION PIGEONPEA (Biological Sciences - PJSIR, 1999)
In a 2-year field trial conducted at Ishurdi, short duration pigeonpea (Cajanus cajan L. Milisp.) responded to the sowing date(15March, 15April, 15May, 15June, 15July,15August, 15September,15October, 15November and 15December).The highestyieldwasobtainedfrom 15Septembersowing,whichalsoproduced thehighestnumber of pods per plant and 1000seed weight. Conpared with the sowing date of 15September, other dates reduced the yield by 22.8 to 207.3%. Days to flowering, days to maturity and plant height declined almost linearly with the progress of sowing dates. September was the optimum time of sowing.